Slow Light with Photonic Crystals for On-Chip Optical Interconnects. (25th June 2008) - Anderson, Sean P.; Shroff, Ashutosh R.; Fauchet, Philippe M.
Abstract : Transistor scaling alone can no longer be relied upon to yield the exponential speed increases we have come to expect from the microprocessor industry. The principle reason for this is the interconnect bottleneck, where the electrical connections between and within microprocessors are becoming, and in some cases have already become, the limiting factor in overall microprocessor performance. Optical interconnects have the potential to address this shortcoming directly, by providing an inter- and intrachip communication infrastructure that has both greater bandwidth and lower latency than electrical interconnects, while remaining safely within size and power constraints. In this paper, we review the requirements that a successful optical interconnect must meet, as well as some of the recent work in our group in the area of slow-light photonic crystal devices for on-chip optical interconnects. We show that slow-light interferometric optical modulators in photonic crystal can have not only high bandwidth, but also extremely compact size. We also introduce the first example of a multichannel slow light platform, upon which a new class of ultracompact optical devices can be built.